Treatment of acidic sulfate-containing wastewater using revolving algae biofilm reactors: Sulfur removal performance and microbial community characterization. (September 2018) - Zhou, Haoyuan; Sheng, Yanqing; Zhao, Xuefei; Gross, Martin; Wen, Zhiyou
Graphical abstract: Highlights: Sulfate-containing wastewater was treated by revolving algae biofilm (RAB) reactors. The RAB reactors had a superior performance of removing sulfur from wastewater. RAB reactors removed sulfate through a consortium of bacteria, cyanobacteria and algae. The RAB reactors effectively removed ammonia, phosphorus, and COD from wastewater. Abstract: Industries such as mining operations are facing challenges of treating sulfur-containing wastewater such as acid mine drainage (AMD) generated in their plant. The aim of this work is to evaluate the use of a revolving algal biofilm (RAB) reactor to treat AMD with low pH (3.5–4) and high sulfate content (1–4 g/L). The RAB reactors resulted in sulfate removal efficiency up to 46% and removal rate up to 0.56 g/L-day, much higher than those obtained in suspension algal culture. The high-throughput sequencing revealed that the RAB reactor contained diverse cyanobacteria, green algae, diatoms, and acid reducing bacteria that contribute the sulfate removal through various mechanisms. The RAB reactors also showed a superior performance of COD, ammonia and phosphorus removal. Collectively, the study demonstrated that RAB-based process is an effective method to remove sulfate in wastewater with small footprint and can be potentially installed in municipal or industrial wastewater treatment facilities.